Pengaruh Pemasangan Exhaust Gas Recirculation Terhadap Emisi Gas Buang Honda Supra X 100 - I Wayan Sugita; Catur Setyawan; Amanda Utari Dewi (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2021)
The increasing demand of motorcycle for humans is directly proportional to the gas emissions by motorcycle. It will cause air condition bad and can cause health problems for humans. One of the solutions for the problem gas emissions produced by motorcycle is doing a modification on exhaust pipe with using Exhaust Gas Recirculation (EGR). This study aims to know the effect of EGR on exhaust gas emission of Honda Supra X 100. The research uses the experimental methods. Emission testing be held to determine the effect after using EGR on the resulting exhaust gas elements by varying the conditions of the mixture (rich and lean), engine speed (1500, 2500, 3500, 4500, 5500 rpm) and fuel (premium, pertalite). The result after using EGR, increased emissions of HC, decreased emissions of CO, increased and decreased CO2 and increased AFR values.